Mapping Plasmodium transitions and interactions in the Anopheles female - Yan Yan; Lisa H. Verzier; Elaine Cheung; Federico Appetecchia; Sandra March; Ailsa R. Craven; Esrah Du; Alexandra S. Probst; Tasneem A. Rinvee; Laura E. de Vries; Jamie Kauffman; Sangeeta N. Bhatia; et al. (Nature, 2025)
Abstract The human malaria parasite, Plasmodium falciparum , relies exclusively on Anopheles mosquitoes for transmission. Once ingested during blood feeding, most parasites die in the mosquito midgut lumen or during epithelium traversal 1 . How surviving ookinetes interact with midgut cells and form oocysts remains poorly understood, yet these steps are essential to initiate a remarkable growth process culminating in the production of thousands of infectious sporozoites 2 . Here, using single-cell RNA sequencing of both parasites and mosquito cells across different developmental stages and metabolic conditions, we unveil key transitions and mosquito–parasite interactions that occur in the midgut. Functional analyses uncover processes that regulate oocyst growth and identify the Plasmodium transcription factor PfSIP2 as essential for sporozoite infection of human hepatocytes. Combining shared mosquito–parasite barcode analysis with confocal microscopy, we reveal that parasites preferentially interact with midgut progenitor cells during epithelial crossing, potentially using their basal location as an exit landmark. Additionally, we show tight connections between extracellular late oocysts and surrounding muscle cells that may ensure parasite adherence to the midgut. We confirm our major findings in several mosquito–parasite combinations, including field-derived parasites. Our study provides fundamental insight into the molecular events that characterize previously inaccessible biological transitions and mosquito–parasite interactions, and identifies candidates for transmission-blocking strategies.